Prevalence of the Antibiotic Resistance Genes in Coagulase-Positive-and Negative-Staphylococcus in Chicken Meat Retailed to Consumers - Osman, Kamelia; Badr, Jihan; Al-Maary, Khalid S.; Moussa, Ihab M. I.; Hessain, Ashgan M.; Girah, Zeinab M. S. Amin; Abo-shama, Usama H.; Orabi, Ahmed; Saad, Aalaa (Frontiers in Microbiology, 2016)
The use of antibiotics in farm management (growing crops and raising animals) has become a major area of concern. Its implications is the consequent emergence of antibiotic resistant bacteria (ARB) and accordingly their access into the human food chain with passage of antibiotic resistance genes (ARG) to the normal human intestinal microbiota and hence to other pathogenic bacteria causative human disease. Therefore, we pursued in this study to unravel the frequency and the quinolone resistance determining region, mecA and cfr genes of methicillin-susceptible Staphylococcus aureus (MSSA), methicillin-resistant S. aureus (MRSA), methicillin-resistant coagulase-negative staphylococci (MRCNS) and methicillin-susceptible coagulase-negative staphylococci (MSCNS) isolated from the retail trade of ready-to-eat raw chicken meat samples collected during one year and sold across the Great Cairo area. The 50 Staphylococcus isolated from retail raw chicken meat were analyzed for their antibiotic resistance phenotypic profile on 12 antibiotics (penicillin, oxacillin, methicillin, ampicillin-sulbactam, erythromycin, tetracycline, clindamycin, gentamicin, ciprofloxacin, chloramphenicol, sulfamethoxazole-trimethoprim and vancomycin) and their endorsement of the quinolone resistance determining region, mecA and cfr genes. The isolation results revealed 50 isolates, CPS (14) and CNS (36), representing ten species (S. aureus, S. hyicus, S. epidermedius, S. lugdunensis, S. haemolyticus, S. hominus, S. schleiferi, S. cohnii, S. intermedius and S. lentus). Twenty seven isolates were methicillin-resistant. Out of the characterized 50 staphylococcal isolates, three were MRSA but only 2/3 carried the mecA gene. The ARG that bestows resistance to quinolones, β-lactams, macrolides, lincosamides and streptogramin B (MLS(B)) in MRSA and MR-CNS were perceived. According to the available literature, the present investigation was a unique endeavor into the identification of the quinolone-resistance-determining-regions, the identification of MRSA and MR-CNS from retail chicken meat in Egypt. In addition, these isolates might indicate the promulgation of methicillin, oxacillin and vancomycin resistance in the community and imply food safety hazards.